Sorry but ur question is wrong..........If I will try to solve it the answer is.........

x∧4a+4b+4c ÷ x∧ax+bx+c

or x=(-3)

Be happy............

The Brainliest Answer!

This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
There seems to be some thing not right in the question.

(x^{a+b})^2 \times (x^{b+c})^2 \times (x^{c+a})^2\\\\= x^{2a+2b}*x^{2b+2c}*x^{2c+2a}=x^{4a+4b+4c}\\\\LHS=x^{4a+4b+4c-a-b-c}=x^{3a+3b+3c}

2 5 2
click on thanks button above please